Antibiotic resistance and serotypes of Streptococcus pneumoniae from patients with community-acquired pneumococcal disease. - Liñares, J (1983)
From August 1978 to December 1981, 200 Streptococcus pneumoniae strains isolated from adult patients with pneumococcal disease were tested for susceptibility to penicillin G, erythromycin, clindamycin, tetracycline, and chloramphenicol by disk diffusion. Minimal inhibitory concentrations (MICs) were determined by agar dilution and broth dilution. The sources (numbers) of these isolates were blood (111), cerebrospinal fluid (30), sputum (26), pleural fluid (16), and miscellaneous (17). Of the 200 strains, 18 were partially resistant (MIC, 0.1 to 1 micrograms/ml) and 2 were resistant to penicillin. A total of 144 (72%) strains were tetracycline resistant, 87 of which had MICs of greater than or equal to 64 micrograms/ml. Ninety (45%) isolates exhibited various degrees of chloramphenicol resistance, with MICs ranging from 16 to 64 micrograms/ml. Five strains were resistant to erythromycin and clindamycin. Eleven penicillin-resistant strains were also resistant to chloramphenicol and tetracycline. Twenty-one different serotypes were encountered among the 120 typed strains studied. The most prevalent serotypes, in order of frequency, were 3, 1, 5, 19, 8, 6, 9, and 4, representing approximately two-thirds of the total number of isolates serotyped. These findings clearly indicate the need to perform antibiotic susceptibility testing in all cerebrospinal fluid isolates and other clinical significant isolates.